Abundance and Distribution Patterns of Oysters (Saccostrea cucullata) in the Bagek Kembar Mangrove Area, West Lombok - Umami, Lia; Karnan, Karnan; Santoso, Didik (Jurnal Biologi Tropis, 2024)
An invertebrate critter called Saccostrea cucullata is typically found adhering to substrates like rocks and mangrove roots. The purpose of this study is to ascertain S. cucullata's abundance and distribution patterns. This study was carried out at West Lombok's Bagek Kembar Sekotong Natural Mangrove Area in February 2024. The samples were observed using the 5 x 5 m quadratic transect approach. To ascertain S. cucullata abundance and dispersion patterns, descriptive analysis was performed on the data. According to the study's findings, station I had the greatest abundance (1.81 Ind/m2), while station III had the lowest (0.95 Ind/m2). S. cucullata exhibits a clustered and uniform distribution pattern in certain areas. In the research region, temperature, salinity, and pH are the main factors affecting S. cucullata abundance and dispersion pattern, respectively.